Xerophilic Alopecosa sulzeri (Pavesi, 1873) (Araneae: Lycosidae)—a new wolf spider species in Poland - Hajdamowicz, Izabela; Rozwałka, Robert; Stańska, Marzena; Rutkowski, Tomasz; Sienkiewicz, Paweł (Zootaxa, 2020)
There are 44 species and subspecies of the genus Alopecosa known in Europe, and 13 of them have so far been listed as occurring in Poland. Alopecosa sulzeri (Pavesi, 1873) is a xero- and thermophilic species distributed in the western Palearctic. In Europe, it occurs primarily in the south-east, while it is rare in Central Europe. Between 2007 and 2013, we recorded the species in the central-eastern, north-western and south-western parts of Poland. The sites of A. sulzeri in Poland are located at the northern limit of the geographic range of the species in Europe. Alopecosa sulzeri was caught at four sites in three regions, exclusively in xerothermic grasslands: in the Podlasie Bug Gorge, the Lower Oder Valley and the Trzebnickie Hills. The sites may be relict, or they may provide evidence of the spread of the species from sites located in neighbouring countries. Further spread of stenotopic, xerophilous A. sulzeri in Poland, if continued, is likely to be a slow process, due to the limited number of suitable habitats.